GUIDELINES FOR DEVELOPING THE PARTICIPATION OF THE EDUCATIONAL INSTITUTION COMMITTEES IN EDUCATIONAL MANAGEMENT OF SCHOOL UNDERSINGBURI PRIMARY EDUCATIONAL SERVICE AREA - Jammee, Juthamard; Techawattanasiridumrong, Wacharapatr (Journal of MCU Nakhondhat, 2020)
The Objectives of this research article were to 1) study the generality problems of the participation of the educational institution committees in educational management of school under Singburi Primary Educational Service Area.2) Offer guidelines for developing the participation of the educational institution committees in educational management of school under Singburi Primary Educational Service Area. The sample group consisted 274 people educational institution committees under Singburi Primary Educational Service Area. The instruments used to research were: questionnaire of guidelines for developing the participation of the educational institution committees in educational management of school under Singburi Primary Educational Service Area. The findings are indicated as follows: 1) The state of the Participation of the Educational Institution committees in educational management of school under Singburi Primary Educational Service Area was generally at the moderate level mean ( = 3.09, S.D. = 0.25). The state of the problems of the participation of the educational institution committees in educational management of school was generally at the low level mean ( = 1.52, S.D. = 0.04). 2) Offer guidelines for developing the participation of the educational institution committees in educational management of school 1) providing information in establishing school curriculum to develop desirable characteristics of students in accordance with local needs percentage 27.00. 2) Developing teachers and personnel for the determination of steps and virtue, building morale of teachers and other personnel percentage 32.80.3 Budget financing materials and equipment providing scholarships to needy students and lacking in order to improve educational management to be most effective and equal percentage 33.60. and 4) To strengthen the relationship between the school and the community allow people to take advantage of the school and to develop the school percentage 47.80.